Mechanistic modelling of allergen-induced airways disease in early life - Hannah J. Pybus; Prakrati Dangarh; Man Yin Melanie Ng; Clare M. Lloyd; Sejal Saglani; Reiko J. Tanaka (Scientific Reports)
Abstract Asthma affects approximately 300 million individuals worldwide and the onset predominantly arises in childhood. Children are exposed to multiple environmental irritants, such as viruses and allergens, that are common triggers for asthma onset, whilst their immune systems are developing in early life. Understanding the impact of allergen exposures on the developing immune system and resulting alterations in lung function in early life will help prevent the onset and progression of allergic asthma in children. In this study, we developed an in silico model describing the pulmonary immune response to a common allergen, house dust mite, to investigate its downstream impact on the pathophysiology of asthma, including airway eosinophilic inflammation, remodelling, and lung function. We hypothesised that altered epithelial function following allergen exposure determines the onset of airway remodelling and abnormal lung function, which are irreversible with current asthma therapies. We calibrated the in silico model using age appropriate in vivo data from neonatal and adult mice. We validated the in silico model using in vivo data from mice on the effects of current treatment strategies. The in silico model recapitulates experimental observations and provides an interpretable in silico tool to assess airway pathology and the underlying immune responses upon allergen exposure. The in silico model simulations predict the extent of bronchial epithelial barrier damage observed when allergen sensitisation occurs and demonstrate that epithelial barrier damage and impaired immune maturation are critical determinants of reduced lung function and asthma development. The in silico model demonstrates that both epithelial barrier repair and immune maturation are potential targets for therapeutic intervention to achieve successful asthma prevention.